Optimization of the optimal hormone formula for kiwifruit and analysis of its storage characteristics - He, Xiaoe; Qin, Wei; He, Qi; Liu, Yunxiang; Wang, Yan; Wang, Rencai; Shi, Hao (Frontiers in Plant Science, 2025)
IntroductionKiwifruit is susceptible to ripening and senescence during postharvest storage, leading to fruit softening, rotting, and nutrient loss, affecting commercial and economic values. Hormones delay senescence by regulating fruit physiology and metabolism, but their specific effects and mechanisms must be further investigated.MethodsTo extend the postharvest storage duration of kiwifruit, we conducted a study using 'Yan Nong 3' kiwifruit as our test material. The fruits were treated with varying concentrations of Brassinolide (BRs), melatonin (MT), methyl jasmonate (MeJA) and salicylic acid (SA), respectively. Subsequently, on the basis of a one-way test, an orthogonal experiment was designed with fruit hardness as an indicator (7 days of storage at room temperature) to obtain the optimal process formulation for phytohormone synergistic treatment (PEHC): 10 μmol·L-1 for BRs, 200 μmol·L-1 for MT, 300 μmol·L-1 for MeJA, and 2 mmol·L-1 for SA.ResultsThe results showed that after 60 days of storage at 4°C, PEHC was found to increase the good fruit rate and the hardness of kiwifruit by 5.97% and 67.42%, respectively, compared to the control. PEHC reduced weight loss rate and disease index, slowed the decrease in titratable acid content (TAC) and vitamin C (VC) content, maintained color, and delayed the accumulation of SSC. At 80 days of storage, the hardness, good fruit rate, VC content, and TAC of PEHC increased by 68.38%, 28.87%, 32.76 mg·100 g-1, and 20.00%, respectively, compared to the control. Whereas, the difference in SSC of PEHC compared to control was nosignificant. The PEHC reduced the content of 1-Aminocyclopropane-1-carboxylate (ACC). Transcriptomics revealed that PEHC inhibited the gene expression levels of Acc08469 in s-adenosylmethionine synthetase (MetK), as well as Acc20538, Acc24995, and Acc17490 in 1-aminocyclopropane-1-carboxylic acid oxidase. Using metabolomics, PEHC increased the relative contents of acids and amino acids and decreased the relative contents of aroma, pigments or phenolics, and soluble sugars compared with the control, of which the trends of changes in acids and soluble sugars were consistently associated with the changes in fruit quality.DiscussionThe PEHC had a favorable effect on maintaining kiwifruit quality and delayed the decline in postharvest storage quality.